Foresight Approach in Developing Strategies and Policies for Natural Resources and Environment Management in Vietnam - Huong, Hoang Thanh (VNU Journal of Science: Policy and Management Studies, 2018)
Vietnam is facing serious environmental and resource issues that directly affect the community. Therefore, in the current context, management must have immediate and long-term orientations in the formulation of strategies and policies; therefore, we need to do well the forecasting work. In contrast to the closed approach of traditional forecasting, the foresight approach is seen as a new way of communicating, exchanging and negotiating among different parts of society, thereby discovering scientific, economic, cultural and social values for contributing to the future society, while integrating the issues to be discussed, evaluated and analyzed in the process of forecasting. As the Vietnamese policy has not achieved the desired effect, the foresight approach can be considered as a new method of forecasting in the development of the natural resources and environment sector’s strategies. Specifically, by reviewing some of the world's major foresight approaches, the paper attempts to answer two questions: (i) How is this approach to be used in the development of the strategy? (ii) To what extent can this approach be applied in forecasting strategy and policy formulation in Vietnam? Based on the answers to these questions, the paper provides recommendations for applying this approach in the development of strategies and policies on natural resources and the environment in Vietnam. Keywords: Foresight, environmental foresight in Vietnam, scenarios method.